PEDAGOGICAL ERUDITION AS A FACTOR IN TRAINING HIGHLY QUALIFIED PERSONNEL. (Universal International Scientific Journal, 2026)
This article considers pedagogical erudition as an important quality of a teacher, which embodies extensive knowledge, professional experience, scientific outlook and creative approach. The study scientifically analyzes its role in improving the quality and efficiency of education, its impact on the process of forming qualified specialists in the modern education system, as well as the prospects and existing problems of developing pedagogical erudition, and justifies the need to improve the professional competence of teachers.
Keywords: pedagogical erudition, quality of education, professional competence, pedagogical skills, innovative education, highly qualified personnel, educational process, pedagogical activity, scientific worldview, pedagogical development